Treatment satisfaction among patients with psoriasis in Saudi Arabia - Mahdi Aldhafiri; Rahaf Almutairi; Reem Albejais; Asma Almubark; Hussain Alwesaibie; Mohammed Albesher; Manayer Almustihi (PAGEPress Publications, 2024)
Psoriasis, affecting 2% of the population, burdens individuals physically and emotionally, with adherence challenges (39-73%). Treatment ranges from topical to systemic therapy including biologics. Although biologic therapy improves clinical outcomes, side effects lead 50% of severe cases to prefer topical treatment. This study evaluates patient satisfaction in Saudi Arabia with various psoriasis treatments, offering insights and addressing the crucial aspect of satisfaction in management. This is a cross-sectional study, using an electronic questionnaire aligned with prior research, included Saudi adults with psoriasis undergoing topical, biological, or phototherapy treatment. Exclusions encompassed non-treatment recipients and participants outside Saudi Arabia. A total of 314 psoriasis patients receiving treatment were included, the most reported types were Plaque psoriasis. The most reported sites of psoriasis included scalp. 70.1% of the patients received topical treatment, 36.3% received systematic treatment, and 18.2% used phototherapy. The participants showed an intermediate satisfaction level, the highest satisfaction for systematic treatments followed by phototherapy and the lowest satisfaction for topical treatments. Male gender, plaque psoriasis, and lack of disease follow-up were associated with poor satisfaction levels.